Training of psychotherapists in post-conflict regions: A Community case study in the Kurdistan Region of Iraq - Beckmann, Julia; Wenzel, Thomas; Hautzinger, Martin; Kizilhan, Jan Ilhan (Frontiers in Psychiatry, 2022)
The number of wars in the world is on the rise. A number of studies have documented the devastating impact on the public and especially public mental health. Health care systems in low- and lower-middle income countries that are frequently already challenged by the existing mental health services gap cannot provide the necessary care for those displaced by war with existing services. This is especially the case in Northern Iraq after the invasion of the terror organization ISIS in 2014. Most projects in post-conflict areas focus on short term basic psychological services and do not contribute to sustainable long-term capacity building of mental health services. An “Institute for Psychotherapy and Psychotraumatology” was therefore founded in order to train local specialists on a professional level with evidence-based methods adapted to culture and create sustainable long-term structures for psychotherapeutic treatment in Northern Iraq. To achieve this, a number of measures were implemented, including the creation of a “Master of Advanced Studies of Psychotherapy and Psychotraumatology” in collaboration with local communities and the regional University. Two cohorts of students have successfully finished the master´s program and a third cohort are expected to graduate in 2023. Improving the capacity of local health care services to provide low-barrier, professional psychotherapeutic care in post-conflict regions supported by the innovative model presented in this article can be expected to improve the burden of psychological problems and contribute to peacebuilding.